Hugo Fontana, en nombre propio - Lucia Campanella (Cuadernos LIRICO)
Los nombres propios. Emir Rodríguez Monegal (2021) is the last novel published during the lifetime of Uruguayan journalist and writer Hugo Fontana (1955-2022), concluding a body of work in which documentary fiction, especially political documentary fiction, holds a prominent place. Published on the occasion of the centenary of the birth of the prominent Uruguayan critic, Los nombres propios combines an extensively documented biography with a crime plot that does not always follow meekly the biographical, and occasionally even hinders it. This article explores how the author's position on the relationship between fiction and history can be traced in this work.